2011
DOI: 10.1117/12.903183
|View full text |Cite
|
Sign up to set email alerts
|

Dielectrophoresis of micro/nano particles using curved microelectrodes

Abstract: Dielectrophoresis, the induced motion of polarisable particles in non-homogenous electric field, has been proven as a versatile mechanism to transport, immobilise, sort and characterise micro/nano scale particle in microfluidic platforms. The performance of dielectrophoretic (DEP) systems depend on two parameters: the configuration of microelectrodes designed to produce the DEP force and the operating strategies devised to employ this force in such processes. This work summarises the unique features of curved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Lab-on-a-chip systems: cell separators Highly efficient lab-on-a-chip systems, specically those used for the detection and separation of microparticles such as cells and viruses, have rapidly progressed through the miniaturization of components and the fabrication of smaller functional devices. [61][62][63] The miniaturization of these systems via the design and fabrication of complex 3D microuidic devices showed new functionality and increased performance. 61,62 Helical geometry has been recently used in the fabrication of highly efficient dielectrophoretic (DEP) cell separators in two different avenues: helical-shaped microelectrodes and helical-shaped microuidic channels.…”
Section: Applicationsmentioning
confidence: 99%
“…Lab-on-a-chip systems: cell separators Highly efficient lab-on-a-chip systems, specically those used for the detection and separation of microparticles such as cells and viruses, have rapidly progressed through the miniaturization of components and the fabrication of smaller functional devices. [61][62][63] The miniaturization of these systems via the design and fabrication of complex 3D microuidic devices showed new functionality and increased performance. 61,62 Helical geometry has been recently used in the fabrication of highly efficient dielectrophoretic (DEP) cell separators in two different avenues: helical-shaped microelectrodes and helical-shaped microuidic channels.…”
Section: Applicationsmentioning
confidence: 99%
“…With the low speeds involved to avoid leakage in the concertation of the sample, the flow of the medium was constant; the flow affects the output result of the DEP fields applied [21]. Additionally, it is a fast, low-voltage magnitude, and potentially low-cost method to extract measurements and to avoid hydrodynamic effects [19,48,49].…”
Section: Discussionmentioning
confidence: 99%
“…In order to achieve a better visualization and detection of bacteria, the integrated DEP microuidic chip was proposed to capture and enrich the target bacteria. [25][26][27][28] Yang et al demonstrated that positive DEP could concentrate Listeria efficiently at the edges the interdigitated micro-electrodes from the ow in microuidic channels. 29 Therefore, bacteria visualizations were worth further study by using highly efficient uorescent markers and an integrated dielectrophoresis microuidic chip.…”
Section: Introductionmentioning
confidence: 99%